ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE (GCG), PRINSIP PEMBIAYAAN, DAN TUJUAN PENGGUNAAN PEMBIAYAAN TERHADAP PEMBIAYAAN BERMASALAH PERBANKAN SYARIAH DI INDONESIA - Hidayat, Dicky Permana; Arfinto, Erman Denny (Diponegoro Journal of Management, 2017)
The largest asset in sharia banking is financing, along with the rapid development of sharia banking, management is required to maximize their assets to increase their profits. Therefore, sufficient knowledge and understanding of financing risks in sharia banking must be owned. This study aims to analyze the influence of Good Corporate Governance (GCG), Financing Principles, and Financing Usage on Non Performing Financing (NPF) of Sharia Banking. The sample used in this research is secondary data from non performing financing (NPF), composite value of corporate governance, Financing Principles (assets based financing and debt based financing), and Financing Usage (working capital financing, investment financing, and consumption financing) for the period 2011-2015. This study uses Multiple Linear Regression Method as the method of analysis. The results of this study indicate that GCG, financing Principles, and Financing Usage affected the level of non performing financing on Islamic Banking in Indonesia. Then the partial test shows debt based financing, investment financing, and consumption financing have a significant positive effect on the level of non performing financing on Islamic Banking in Indonesia.